PENGAMBILAN KEPUTUSAN DAN POLA PEMBELIAN BUMBU GILING PADA RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Elisa Sijabat; Wuryaningsih Dwi Sayekti; Dyah Aring Hepiana Lestari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this research are to determine the decision making process, purchasing patterns, and dominant factors in purchasing ground spices in Kota Bandar Lampung. This research was conducted in Pasir Gintung market, Tugu market, and Cimeng market. There were 90 housewife respondents drawn using accidental sampling method. Ground spices, as the object of this research, consisted of “sayur santan”, “rendang” and “ungkep” spices. Data were analyzed descriptively and using Principal Component Analysis (PCA) factor analysis. The results showed that housewives decided to buy ground spices by the process of needs introduction, information searching, alternative evaluation, purchase decision, and post-purchase evaluation. The pattern of ground spices purchases by housewives was that the amount of spice purchased in the past week was IDR2,000.00- IDR5,500.00, the most type purchased was “rendang” with the frequency of 1-2 times a week. The dominant factors on purchasing decisions was formed by three main factors based on the value of the loading factors. The first, influence factor, consisted of variables colour, taste, influence of other people, confidence of making seasoning by their own, and confidence in taste of ground spices. The second, perception factor, consisted of variables perception of the price compared to the amount of ground spices obtained, perception of the price compared to that of packaged ground seasoning, and aroma of ground spices. The third, display of ground spices business, consisted of variables cleanliness of the product, the place, and friendliness of traders.Key words: factor, ground spices, purchase